Comparative biocompatibility of hydrophilic vs. hydrophobic intraocular lenses following phacoemulsification in patients with uveitis - Atitaya Apivatthakakul; Apichat Tantraworasin; Paradee Kunavisarut; Kessara Pathanapitoon (PLoS ONE, 2025)
Purpose To evaluate and compare the biocompatibility of hydrophilic and hydrophobic intraocular lenses (IOLs) in patients with uveitis undergoing phacoemulsification, with particular focus on posterior capsule opacification (PCO), postoperative inflammation, and visual outcomes. Methods Patients with uveitis who underwent phacoemulsification with IOL implantation between 2015 and 2023 were retrospectively reviewed. Propensity score matching (1:1) was performed to account for clinical and demographic variables, yielding 132 eyes (66 per group) for analysis. Primary outcomes included the incidence of PCO and the need for neodymium-doped yttrium aluminum garnet (Nd:YAG) laser capsulotomy. Secondary outcomes were the rate of uveitis reactivation and visual improvement. Cox regression models were used to estimate adjusted hazard ratios (HRs) with 95% confidence intervals (CIs). Results Hydrophobic IOLs were significantly associated with a reduced risk of PCO (adjusted HR = 0.35; 95% CI, 0.18–0.68; p < 0.05) and Nd:YAG capsulotomy (adjusted HR = 0.23; 95% CI, 0.09–0.56; p < 0.05) compared to hydrophilic IOLs. No significant difference was found in the rate of uveitis reactivation between groups (adjusted HR = 0.83; 95% CI, 0.37–1.88; p = 0.643). Conclusion Hydrophobic intraocular lenses show better capsular biocompatibility in uveitic eyes by significantly reducing the incidence of PCO and need for Nd:YAG capsulotomy, without increasing postoperative inflammation. These findings support the preferential use of hydrophobic acrylic IOLs in cataract surgery for patients with uveitis.